RELATIONSHIP OF ENVIRONMENTAL CONDITIONS AND HYGIENE BEHAVIOR WITH THE INCIDENCE OF ISPA IN CHILDREN UNDER FIVE IN THE REGION OF PUSKESMAS DUDUK SAMPEYAN GRESIK - Putri Prasetyati Ningrum; Hindyah Ike; Nurul Huda (Jurnal Keperawatan, 2014)
Health problem that often occurs in children and is likely to increase each year of acute respiratory tract infections. Environment that is close to the highway, the less maintained home hygiene and health behaviors such as unbalanced diet, lack of rest and smoking habits of parents in the home can cause respiratory infection in infants. The purpose of this study was to determine the relationship of environmental conditions and hygiene behavior with the incidence of ISPA in children under five in the region of Puskesmas Duduk Sampeyan Gresik. This type of research is non-experimental cross-sectional approach. The population is all mothers who have children aged 1-4 years in rural Brak Tebaloan Duduk Sampeyan Gresik as 58 people. Study sample were 51 mothers and taken by using purposive sampling technique. Data processed by the editing, coding, scoring, and tabulating and Test Correlation with Spearman Rank with significance level α = 0.05. The results showed that there is a relationship of environmental conditions with the incidence of ISPA in infants with Spearman rank test p value = 0.005 <α = 0.05, which means that H1 is accepted, and the hygiene behavior of the research results with the incidence of respiratory infection in infants p value = 0.014 <α = 0.05, which means that H2 is accepted.The results of this research that there is a relationship of environmental conditions and hygiene behavior with the incidence of ISPA in children under five in the Village Brak Tebaloan Duduk Sampeyan Gresik.Suggestion for this study include health workers to do more counseling about a healthy environment, for the health of mothers and children to always maintain good environmental conditions and healthy living behavior in order to familiarize the child avoid the disease, especially respiratory infectionKeyword : Environmental conditions, hygiene Behavior, ISPA